The Success Rate of Endotracheal Intubation in the Emergency Department of Tertiary Care Hospital in Ethiopia, One-Year Retrospective Study - Ayalew Zewdie; Dejene Tagesse; Selam Alemayehu; Tesfaye Getachew; Menbeu Sultan (Emergency Medicine International)
Background. Emergency medical care starts with airway assessment and intervention management. Endotracheal intubation is the definitive airway management in the emergency department (ED) for patients requiring a definitive airway. Successful first pass is recommended as the main objective of emergency intubation. There exists no published research regarding the success rates or complications that occur within Ethiopian hospitals emergency department intubation practice. Objective. This study aimed to assess the success rate of emergency intubations in a tertiary hospital, Addis Ababa, Ethiopia. Methodology. This was a single institute retrospective documentation review on intubated patients from November 2017 to November 2018 in the emergency department of Addis Ababa Burn Emergency and Trauma Hospital. All intubations during the study period were included. Data were collected by trained data collectors from an intubation documentation sheet. Result. Of 15,933 patients seen in the department, 256 (1.6%) patients were intubated. Of these, 194 (74.9%) were male, 123 (47.5%) sustained trauma, 65 (25.1%) were medical cases, and 13(5%) had poisoning. The primary indications for intubation were for airway protection (160 (61.8%)), followed by respiratory failure (72(27.8%)). One hundred and twenty-nine (49.8%) had sedative-only intubation, 110 (42.5%) had rapid sequence intubation, and 16 (6.2%) had intubation without medication. The first-pass success rate in this sample was 70.3% (180/256), second-pass 21.4% (55/256), and third-pass 7.4% (19/256), while the overall success rate was 99.2% (254/256). Hypoxia was the most common complication. Conclusion. The intubation first-pass success rate was lower than existing studies, but the overall intubation success rate was satisfactory.